Utilization of local plants for fish disease control: systematic literature review - Salmiati Salmiati; Ratna Sari; Muhammad Hidayatullah; Amelia Sriwahyuni Lubis; Ira Desmiati (Acta Aquatica: Aquatic Sciences Journal, 2026)
Fish farming is one of the most popular activities in the community. However, a common obstacle for fish farmers is the attack of diseases that attack cultured fish. Bacterial infection is one example of a disorder that often attacks farmed fish and causes losses in fish farming. Due to side effects and drug resistance, the use of chemical drugs and antibiotics in fish has been restricted. On the other hand, efforts can be made to improve the prevention and treatment of fish diseases by the use of herbal plants. This article discusses studies on the use of herbal materials that enhance fish immunity and resistance to bacterial diseases and focuses on the types of herbal plants. The review results show that the use of herbal plants for the management and control of diseases affecting fish populations effectively shows a higher level of efficiency and poses a much lower risk to the health of aquatic organisms and can be a more economical alternative when compared to frequently used chemical drugs. Keywords: Aquaculture; Chemical; Disease; Local Plants